2012
DOI: 10.1088/0268-1242/27/11/115011
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of fluence-dependent photocurrent in terahertz photoconductive receivers

Abstract: A semi-classical Monte Carlo simulation of carrier dynamics in photoconductive detectors of terahertz (THz) radiation is presented. We have used this simulation to elucidate the importance of carrier trapping in the operation of photoconductive detectors. Simulations of the detection of single-cycle THz pulses by photoconductive antennas based on GaAs with trap densities between 2 × 10 17 and 2 × 10 18 cm −3 are presented. We show that the high frequency (>1 THz) spectral response of photoconductive devices de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Scattering is supposed to increase due to the excitation of LO-phonons and a higher carrier density [14,23]. Hereby the former make the major contribution, since Monte Carlo-simulations have shown that carrier-to-carrierscattering plays only a minor role, being of elastic nature and thus only causing slight angular deviations of carrier trajectories [24]. Whereas a rise of pulsed optical power merely results in an increase of involved carriers, CW-excited carrier contribution is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Scattering is supposed to increase due to the excitation of LO-phonons and a higher carrier density [14,23]. Hereby the former make the major contribution, since Monte Carlo-simulations have shown that carrier-to-carrierscattering plays only a minor role, being of elastic nature and thus only causing slight angular deviations of carrier trajectories [24]. Whereas a rise of pulsed optical power merely results in an increase of involved carriers, CW-excited carrier contribution is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the boundary conditions are described in [20] with the Eqs. (23) and (24). Taking into consideration all these contributions, we can calculate the flowing through the metal contacts on the surface S Ω by means of the following equation [shown in Fig.…”
Section: Numerical Algorithms To Implement the Reception Process Analmentioning
confidence: 99%
“…The PCA emission has been already studied [14][15][16][17][18][19][20]. There are numerical and experimental studies of receivers based on PCAs [19,[21][22][23][24]; however, as far as we know, the lack of simultaneously simple and accurate numerical methods to simulate reception processes is one of the issues of major concern in THz-TDS and THz-I studies. That is what we do here; for the development of the numerical method presented we have dealt with the usual trade-off, simplicity versus accuracy, in order to address a realistic description of a receiver within a feasible and reasonable numerical approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scattering is supposed to increase due to the excitation of longitudinal optical (LO)-phonons and a higher carrier density [137,148]. Hereby the former make the major contribution, since Monte Carlo-simulations have shown that carrier-to-carrierscattering plays only a minor role, being of elastic nature and thus only causing slight angular deviations of carrier trajectories [149]. Whereas a rise of pulsed optical power merely results in an increase of involved carriers, CW-excited carrier contribution is negligible.…”
Section: Discussionmentioning
confidence: 99%